The role of Sirt6 in osteoarthritis and its effect on macrophage polarization. Issue 4 (1st April 2022) - Chen, Jinwei; Chen, Sichun; Cai, Dawei; Wang, Qiugen; Qin, Jian
ABSTRACT: Osteoarthritis (OA), the commonest arthritis type, features irreversible cartilage loss and synovitis. It was reported that macrophages have an important function in synovial inflammation, and our team revealed that the amounts of Sirt6, a nicotinamide adenine dinucleotide (NAD) + -dependent histone deacetylase, decrease during synovial inflammation and osteoarthritis. This work aimed to examine the anti-inflammatory properties of Sirt6 in synovial inflammation. Firstly, we compared Sirt6 amounts in acute meniscus injury and OA human knee synovial tissue samples by immunofluorescence and immunoblot. Secondly, Sirt6ʹs suppressive effects on inflammatory markers and macrophage polarization were evaluated. Finally, OA mice were histologically evaluated, and serum inflammatory factors were detected for assessing the impact of Sirt6 overexpression on the mouse synovium. We found significantly lower interleukin-4 (IL-4) amounts and M2 polarization in OA patients compared with control individuals. The expression of Sirt6 was lower in RAW264.7 cells of the lipopolysaccharides (LPS) + interferon-gamma (IFN-γ) group compared with the phosphate buffer saline (PBS) group, but higher than in the IL-4 group. The polarization of macrophages affected Sirt6 expression, which was reduced and elevated in M1 and M2 macrophages, respectively. Sirt6 inhibition could promote the release of proinflammatory cytokines by macrophages in the synovial membrane, induce M1 polarization in macrophages and inhibit M2 polarization in vitro, and Sirt6 overexpression alleviated osteoarthritis in vivo . These data strongly suggested that Sirt6 could inhibit synovial inflammation. Thus, this study provides a novel therapeutic target in osteoarthritis. Graphical abstract: uf0001